Hydrophobic zeolite / cement / silica sol composite microsphere and preparation method thereof
Through the preparation of hydrophobic zeolite/cement/silica sol composite microspheres, the problems of high water vapor adsorption amount and cost of existing gas adsorption materials are solved, and the VOCs gas is efficiently adsorbed, which is suitable for air purification and cultural relics protection.
Patent Information
- Application Number
- CN202411230690.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-04
AI Technical Summary
Existing gas adsorbent materials tend to preferentially adsorb water during use, resulting in a decrease in active adsorption sites, a reduction in the treatment performance of pollutants in the air, and the need to roast after granulation increases cost and energy consumption, limiting their large-scale promotion and application.
The preparation method of hydrophobic zeolite/cement/silica sol composite microspheres is adopted to react natural zeolite with acid solution to form high silicate zeolite, and mixed with cement and silica sol, and then impregnate in coupling agent solution to form high hydrophobicity. and composite microspheres with excellent gas adsorption properties.
Gas adsorption materials with low water vapor adsorption, high VOCs gas adsorption, low cost, simple process and low energy consumption are achieved, and are suitable for air purification and cultural relics protection.
Smart Images

Figure CN119143466A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to natural zeolite modification, in particular to hydrophobic zeolite / cement / silica sol composite microspheres and a preparation method thereof. Background Art
[0002] With the rapid development of social economy, a large amount of pollutants are continuously discharged, resulting in an increasingly serious threat to the earth's ecological environment. In particular, fuel combustion, chemical production, waste incineration and volatilization of decoration materials produce a large amount of VOCs and other pollutant gases, making the air pollution problem particularly prominent. Therefore, how to develop a material that can effectively absorb these harmful gases has become a hot topic of concern.
[0003] At present, researchers are constantly seeking and developing new air purification technologies and materials in order to solve the problem of air pollution. Among the many air purification materials, gas adsorption materials have received special attention due to their advantages such as simple preparation process, convenience and high efficiency. Some new gas adsorption materials, such as activated carbon and zeolite molecular sieves, have been widely used. However, most gas adsorption materials still have two key problems in practical applications: First, the adsorption materials currently used often preferentially adsorb water during use, resulting in a reduction in their active adsorption sites and reduced performance in treating pollutants in the air; second, adsorption materials generally need to be formed and granulated before they can be used, but most granular adsorbents need to be calcined after granulation to increase their strength, resulting in increased costs and energy consumption, which is not conducive to large-scale promotion and application.
[0004] Therefore, how to develop a gas adsorption material with low water vapor adsorption, high adsorption of pollutant gases such as VOCs, low cost, simple process and low energy consumption is still an important issue that needs to be studied and solved in depth. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a hydrophobic zeolite / cement / silica sol composite microsphere and a preparation method thereof, which not only has a simple process, low energy consumption and a high molding rate, but also the prepared microspheres have good mechanical strength, high hydrophobicity and excellent volatile organic gas adsorption performance.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing hydrophobic zeolite / cement / silica sol composite microspheres comprises the following steps:
[0008] Step 1, according to the ratio (80-160g): 1L, take natural zeolite and acid solution with a concentration of 3-8mol / L and mix them, react at 70-90°C for 12-48h, then wash, filter, dry and grind in sequence to obtain high-silicon zeolite;
[0009] Step 2, according to the ratio of (600-1000g): (80-160g): 1L, high-silicon zeolite, cement and silica sol gelling material are mixed and stirred evenly, and then loaded into a mold, and after solidification, demoulding and drying in the shade in sequence to obtain zeolite / cement / silica sol composite microspheres;
[0010] Step 3: first dissolve the coupling agent in alcohol to prepare a coupling agent / alcohol solution with a concentration of 0.05% to 10%, and then immerse the zeolite / cement / silica sol composite microspheres in the coupling agent / alcohol solution at room temperature for 24 to 48 hours to obtain hydrophobic zeolite / cement / silica sol composite microspheres.
[0011] Furthermore, the natural zeolite in step 1 is natural clinoptilolite or natural mordenite.
[0012] Furthermore, the acid solution in step 1 is a nitric acid solution or a hydrochloric acid solution.
[0013] Furthermore, in the step 1, the molar ratio of silicon to aluminum of the high-silicon zeolite is 16.6 to 21.8.
[0014] Furthermore, the coupling agent in step 3 is dodecyltrimethylsilane, dodecyl(methyl)dimethoxysilane, dodecyltrichlorosilane or dodecyldimethylchlorosilane.
[0015] Furthermore, the alcohol in step 3 is methanol, ethanol or propanol.
[0016] A hydrophobic zeolite / cement / silica sol composite microsphere, with a water contact angle of 105.2° to 120°.
[0017] Furthermore, the water vapor absorption capacity is 3.85 to 5.21 mg / g, and the acetic acid adsorption capacity is 37.86 to 40.25 mg / g.
[0018] Compared with the prior art, the present invention has the following technical effects:
[0019] Firstly, the present invention uses an acid solution to modify cheap and readily available natural zeolite to obtain high-silicon zeolite with high specific surface area and porosity, thereby effectively improving the gas adsorption performance of the zeolite; secondly, the high-silicon zeolite is mixed with cement and silica sol gelling materials, and the cement and silica sol can effectively bond the zeolite particles to achieve uniform mixing between the particles. The obtained zeolite / cement / silica sol composite microspheres have abundant pores and are rich in hydroxyl active groups; thirdly, the zeolite / cement / silica sol composite microspheres are completely immersed in an alcohol solution of an organic coupling agent for modification, and the hydroxyl groups on the surface of the composite microspheres are bonded with the coupling agent, thereby obtaining highly hydrophobic zeolite / cement / silica sol composite microspheres; in short, the present invention not only has the advantages of cheap and readily available materials, simple preparation process, easy to control reaction conditions, green environmental protection and low energy consumption, but also the prepared highly hydrophobic zeolite / cement / silica sol composite microspheres have the advantages of low water vapor adsorption and high adsorption of gaseous pollutants such as VOCs, can be repeatedly used to adsorb indoor VOCs pollutants, and are very suitable for the fields of cultural relics protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 : XRD patterns of natural clinoptilolite, zeolite / cement / silica sol composite microspheres prepared in Example 1, and hydrophobic zeolite / cement / silica sol composite microspheres;
[0021] Figure 2(a): SEM image of natural clinoptilolite;
[0022] Figure 2(b): EDX spectrum of natural clinoptilolite;
[0023] Figure 2(c): SEM image of high-silicon zeolite prepared in Example 1;
[0024] FIG2( d ) is an EDX spectrum of the high-silicon zeolite prepared in Example 1;
[0025] FIG3( a ) is a line graph showing moisture absorption and moisture release of zeolite / cement / silica sol composite microspheres and hydrophobic zeolite / cement / silica sol composite microspheres prepared in Example 1;
[0026] Figure 3(b): Line graph of VOCs adsorption of zeolite / cement / silica sol composite microspheres and hydrophobic zeolite / cement / silica sol composite microspheres prepared in Example 1;
[0027] FIG4(a) shows the compressive strength curve of the zeolite / cement / silica sol specimen prepared according to the process parameters of Example 1 and cured for 3 days;
[0028] FIG4( b ) shows the compressive strength curve of the zeolite / cement / silica sol specimen prepared according to the process parameters of Example 1 and cured for 7 days;
[0029] FIG5( a ) shows the water contact angle of the hydrophobic zeolite / cement / silica sol composite microspheres prepared in Example 1;
[0030] Figure 5(b): Water contact angle of zeolite / cement / silica sol composite microspheres prepared in Example 1;
[0031] Figure 6 : SEM images of zeolite / cement / silica sol composite microspheres prepared in Example 1 at different magnifications;
[0032] FIG7( a ) is an EDX spectrum of the zeolite / cement / silica sol composite microspheres prepared in Example 1;
[0033] Figure 7(b): Element distribution diagram of zeolite / cement / silica sol composite microspheres prepared in Example 1;
[0034] Figure 8 : SEM images of the hydrophobic zeolite / cement / silica sol composite microspheres prepared in Example 1 at different magnifications;
[0035] FIG9( a ) is an EDX spectrum of the hydrophobic zeolite / cement / silica sol composite microspheres prepared in Example 1;
[0036] FIG9( b ): Element distribution diagram of the hydrophobic zeolite / cement / silica sol composite microspheres prepared in Example 1;
[0037] Fig.10 : Actual picture of the hydrophobic zeolite / cement / silica sol composite microspheres prepared in Example 1. DETAILED DESCRIPTION
[0038] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0039] The preparation method of the silica sol gelling material involved in Examples 1 to 37 of the present invention can be found in Chinese invention patent application number CN2024101515494 (publication number CN117797768A).
[0040] The cement involved in Examples 1 to 37 of the present invention is commercially available white cement, ordinary Portland cement or composite cement.
[0041] Example 1
[0042] Step 1: Preparation of high-silicon zeolite
[0043] Take 10g of natural zeolite and add 100mL of 6mol / L nitric acid solution, stir at 80°C for 48h, then wash, filter, dry and grind in sequence to obtain high-silicon zeolite;
[0044] Step 2: Preparation of zeolite / cement / silica sol composite microspheres
[0045] According to the ratio of 800g:100g:1L, high silicon zeolite, white cement and silica sol gelling material are mixed and stirred evenly, and then loaded into a mold, and solidified, demoulded and dried in the shade in sequence to obtain zeolite / cement / silica sol composite microspheres;
[0046] Step 3: Preparation of hydrophobic zeolite / cement / silica sol composite microspheres
[0047] First, dodecyltrimethylsilane was dissolved in methanol to prepare a 0.5% dodecyltrimethylsilane / methanol solution, and then the zeolite / cement / silica sol composite microspheres were immersed in the dodecyltrimethylsilane / methanol solution at room temperature, and the mixture was allowed to stand for 24 hours to obtain the following: Fig.10 The hydrophobic zeolite / cement / silica sol composite microspheres shown.
[0048] Depend on Figure 1 From the XRD spectrum of the samples, it can be seen that natural zeolite mainly contains minerals such as clinoptilolite and quartz; the intensity of the characteristic peak of clinoptilolite in the XRD spectrum of high-silicon zeolite is significantly reduced, indicating that its crystallinity is reduced, which is mainly due to the removal of part of the aluminum in the clinoptilolite by acid treatment; in addition to the characteristic peaks of clinoptilolite and quartz, the XRD spectrum of zeolite / cement / silica sol composite microspheres also has characteristic peaks such as tricalcium silicate and calcium hydroxide, which mainly come from the cement component in the composite microspheres; the intensity of the characteristic peaks of each phase in the XRD spectrum of hydrophobic zeolite / cement / silica sol composite microspheres is weakened, which is due to the surface modification of silane coupling agent.
[0049] Figure 2(a) is a SEM photo of natural zeolite, from which it can be seen that the natural zeolite particles are irregular in shape, with particle sizes ranging from a few microns to hundreds of nanometers; Figure 2(b) shows the EDX spectrum analysis results of natural zeolite, showing that the Si / Al ratio on the sample surface is about 5.4; Figure 2(c) is a SEM photo of high-silicon zeolite, from which it can be seen that the morphology of high-silicon zeolite particles has not changed significantly compared with that of natural zeolite; Figure 2(d) shows the EDX spectrum analysis results of high-silicon zeolite, showing that the Si / Al ratio on the sample surface is 20.5, which is much higher than that of natural zeolite samples.
[0050] 10 g of the zeolite / cement / silica sol composite microsphere sample and the hydrophobic zeolite / cement / silica sol composite microsphere sample prepared in Example 1 were placed in a culture dish, and the culture dish was then placed in a drying dish containing a saturated potassium chloride salt solution. A moisture absorption experiment was performed at 28° C. The samples were taken out and weighed at regular intervals. After moisture absorption equilibrium was reached, the moisture absorption amount was calculated. As shown in FIG. 3( a), the moisture absorption amounts of the zeolite / cement / silica sol composite microsphere and the hydrophobic zeolite / cement / silica sol composite microsphere were 23.79 mg / g and 4.67 mg / g, respectively, indicating that the zeolite / cement / silica sol composite microsphere modified with a 0.5% dodecyltrimethylsilane / methanol solution had good hydrophobicity.
[0051] 10 g of the zeolite / cement / silica sol composite microsphere sample and the hydrophobic zeolite / cement / silica sol composite microsphere sample prepared in Example 1 were placed in a culture dish, and the culture dish was then placed in a drying dish containing saturated glacial acetic acid. An adsorption experiment was performed at 28° C. The samples were taken out and weighed at regular intervals. After moisture absorption equilibrium was reached, the amount of acetic acid adsorbed was calculated. The results are shown in FIG. 3( b). The amount of acetic acid adsorbed by the zeolite / cement / silica sol composite microsphere and the hydrophobic zeolite / cement / silica sol composite microsphere were 37.96 mg / g and 38.68 mg / g, respectively, indicating that they have good adsorption properties for volatile gases.
[0052] According to the ratio of 800g:100g:1L, high-silicon zeolite, cement and silica sol gelling material were mixed and stirred evenly, then loaded into a cylindrical mold with a diameter of 50cm and a height of 25cm, and fully oscillated to mix them evenly. The mold containing the sample was sealed with plastic wrap and cured at room temperature for 3 days and 7 days. The compressive strength of the sample blocks was tested, respectively. See Figure 4(a) and Figure 4(b). The strength of the sample blocks cured for 3 days and 7 days was 1.18Mpa and 3.68MPa, respectively, indicating that they have good compressive resistance and are not easily broken during use.
[0053] As can be seen from Figures 5(a) and 5(b), the water contact angle of the hydrophobic zeolite / cement / silica sol composite microspheres prepared in Example 1 is 110.2°, and the water contact angle of the zeolite / cement / silica sol composite microspheres is 18.4°, proving that the zeolite / cement / silica sol composite microspheres have good hydrophobicity after being modified with a 0.5% dodecyltrimethylsilane / methanol solution.
[0054] from Figure 6 It can be seen that the surface of the zeolite / cement / silica sol composite microspheres prepared in Example 1 has many voids, which is conducive to the adsorption of water vapor. As can be seen from Figure 7(a), its Si / Al ratio is 48.3. As can be seen from Figure 7(b), the sample surface contains elements such as Si, Al, Ca, Na, C and O.
[0055] from Figure 8 It can be seen that there are many needle-like objects on the surface of the hydrophobic zeolite / cement / silica sol composite microspheres prepared in Example 1, which are coupling agents distributed on the surface of the zeolite / cement / silica sol composite microspheres, and can give the zeolite / cement / silica sol composite microspheres good hydrophobicity, thereby preferentially adsorbing VOCs harmful gases; as can be seen from Figure 9(a), its Si / Al ratio is 58.2, and as can be seen from Figure 9(b), the sample surface contains elements such as Si, Al, Ca, Na, C and O.
[0056] Example 2 to Example 37
[0057] The difference between Examples 2 to 37 and the Examples is that the types of raw materials, proportions and reaction conditions are different, see Table 1 for details.
[0058] The silicon / aluminum molar ratio of the high-silicon zeolite prepared in Examples 2 to 37 is 16.6 to 21.8, see Table 2 for details.
[0059] The contact angles of the hydrophobic zeolite / cement / silica sol composite microspheres prepared in Examples 2 to 37 are 105.2° to 120°, see Table 3 for details.
[0060] 5 g of the zeolite / cement / silica sol composite microsphere samples and the hydrophobic zeolite / cement / silica sol composite microsphere samples prepared in Examples 2 to 37 were respectively placed in a culture dish, and the culture dish was then placed in a drying dish containing a saturated potassium chloride salt solution. A moisture absorption experiment was performed at 28°C. The samples were taken out and weighed at regular intervals. After moisture absorption equilibrium was reached, the moisture absorption was calculated. The results are shown in Tables 4-1 and 4-2. The moisture absorption of the zeolite / cement / silica sol composite microspheres was 22.15 to 24.25 mg / g, and the moisture absorption of the hydrophobic zeolite / cement / silica sol composite microspheres was only 3.85 to 5.21 mg / g.
[0061] 5 g of the zeolite / cement / silica sol composite microsphere samples and the hydrophobic zeolite / cement / silica sol composite microsphere samples prepared in Examples 2 to 37 were respectively placed in a culture dish, and the culture dish was then placed in a drying dish containing saturated glacial acetic acid. An adsorption experiment was performed at 28°C. The samples were taken out and weighed at regular intervals. After moisture absorption equilibrium was reached, the adsorption amount of acetic acid was calculated. The results are shown in Tables 4-1 and 4-2.
[0062] It can be seen from Table 4-1 and Table 4-2 that the acetic acid adsorption capacity of the zeolite / cement / silica sol composite microspheres prepared in Examples 2 to 37 is 37.65 to 40.25 mg / g; the acetic acid adsorption capacity of the hydrophobic zeolite / cement / silica sol composite microspheres is 37.86 to 40.25 mg / g.
[0063] According to the proportions and parameters of Example 2 to Example 37 in Table 1, high-silicon zeolite, cement and silica sol gelling materials were taken respectively, loaded into a cylindrical mold with a diameter of 50 cm and a height of 25 cm, and 36 test blocks of the same specifications were made. They were cured at room temperature for 3 days and 7 days respectively, and the compressive strength was tested respectively. The results are shown in Tables 5 and 6;
[0064] It can be seen from Tables 5 and 6 that the compressive strength of the sample blocks cured for 3 days is 1.05-1.57 MPa; the compressive strength of the sample blocks cured for 7 days is 3.24-4.58 MPa, indicating that the zeolite / cement / silica sol composite microspheres prepared in Examples 2 to 37 have good compressive resistance.
[0065] Table 1: Raw materials and their proportions and reaction conditions of Examples 2 to 37
[0066]
[0067]
[0068]
[0069] Table 2: Silicon to aluminum ratio of high silicon zeolites prepared in Examples 2 to 37
[0070] Example Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Example 10 Silicon to aluminum ratio 20.5 16.6 18.4 25.4 20.5 20.4 20.8 20.4 21.1 Example Embodiment 11 Example 12 Example 13 Embodiment 14 Embodiment 15 Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Silicon to aluminum ratio 20.1 20.5 20.6 20.5 20.7 20.4 20.1 20.6 20.4 Example Embodiment 20 Embodiment 21 Embodiment 22 Embodiment 23 Embodiment 24 Embodiment 25 Embodiment 26 Embodiment 27 Embodiment 28 Silicon to aluminum ratio 20.4 20.3 20.1 20.6 20.4 20.1 20.5 20.9 20.7 Example Embodiment 29 Embodiment 30 Embodiment 31 Embodiment 32 Embodiment 33 Embodiment 34 Embodiment 35 Embodiment 36 Embodiment 37 Silicon to aluminum ratio 20.6 20.5 20.4 20.6 20.7 20.5 21.8 21.5 21.1
[0071] Table 3: Surface water drop contact angle of hydrophobic zeolite / cement / silica sol composite microspheres prepared in Examples 2 to 37
[0072] Example Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Example 10 Contact Angle 105.2 108.5 110.2 110.8 115.2 115.6 118.5 119.2 120 Example Embodiment 11 Example 12 Example 13 Embodiment 14 Embodiment 15 Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Contact Angle 108.2 110.3 110.6 110.8 110.5 110.9 115.8 116.3 116.9 Example Embodiment 20 Embodiment 21 Embodiment 22 Embodiment 23 Embodiment 24 Embodiment 25 Embodiment 26 Embodiment 27 Embodiment 28 Contact Angle 110.9 116.2 105.9 118.5 119.6 116.3 115.2 115.2 112.2 Example Embodiment 29 Embodiment 30 Embodiment 31 Embodiment 32 Embodiment 33 Embodiment 34 Embodiment 35 Embodiment 36 Embodiment 37 Contact Angle 110.5 111.2 116.2 113.2 111.2 111.5 115.2 118.2 114.1
[0073] Table 4-1: Moisture absorption and acetic acid adsorption of zeolite / cement / silica sol composite microspheres prepared in Examples 2 to 37
[0074]
[0075]
[0076] Table 4-2: Moisture absorption and acetic acid adsorption of hydrophobic zeolite / cement / silica sol composite microspheres prepared in Examples 2 to 37
[0077]
[0078] Table 5: Compressive strength of the test pieces prepared according to the process parameters of Examples 2 to 19
[0079]
[0080] Table 6: Compressive strength of the test pieces prepared according to the process parameters of Examples 20 to 37
[0081]
Claims
1. A method for preparing hydrophobic zeolite / cement / silica sol composite microspheres, characterized in that: The steps include: Step 1, according to the ratio (80-160g): 1L, take natural zeolite and acid solution with a concentration of 3-8mol / L and mix them, react at 70-90°C for 12-48h, then wash, filter, dry and grind in sequence to obtain high-silicon zeolite; Step 2, according to the ratio of (600-1000g): (80-160g): 1L, high-silicon zeolite, cement and silica sol gelling material are mixed and stirred evenly, and then loaded into a mold, and after solidification, demoulding and drying in the shade in sequence to obtain zeolite / cement / silica sol composite microspheres; Step 3: first dissolve the coupling agent in alcohol to prepare a coupling agent / alcohol solution with a concentration of 0.05% to 10%, and then immerse the zeolite / cement / silica sol composite microspheres in the coupling agent / alcohol solution at room temperature for 24 to 48 hours to obtain hydrophobic zeolite / cement / silica sol composite microspheres.
2. The method for preparing hydrophobic zeolite / cement / silica sol composite microspheres according to claim 1, characterized in that: The natural zeolite in step 1 is natural clinoptilolite or natural mordenite.
3. The method for preparing hydrophobic zeolite / cement / silica sol composite microspheres according to claim 1, characterized in that: The acid solution in step 1 is a nitric acid solution or a hydrochloric acid solution.
4. The method for preparing hydrophobic zeolite / cement / silica sol composite microspheres according to claim 1, characterized in that: The silicon / aluminum molar ratio of the high-silicon zeolite in step 1 is 16.6 to 21.
8.
5. The method for preparing hydrophobic zeolite / cement / silica sol composite microspheres according to claim 1, characterized in that: The coupling agent in step 3 is dodecyltrimethylsilane, dodecyl(methyl)dimethoxysilane, dodecyltrichlorosilane or dodecyldimethylchlorosilane.
6. The method for preparing hydrophobic zeolite / cement / silica sol composite microspheres according to claim 1, characterized in that: The alcohol in step 3 is methanol, ethanol or propanol.
7. A hydrophobic zeolite / cement / silica sol composite microsphere prepared by the method according to any one of claims 1 to 6, characterized in that: The water contact angle is 105.2°~120°.
8. The hydrophobic zeolite / cement / silica sol composite microsphere according to claim 7, characterized in that: The water vapor absorption capacity is 3.85-5.21 mg / g, and the acetic acid adsorption capacity is 37.86-40.25 mg / g.
Citation Information
Patent Citations
Method for preparing lyophobic silicon dioxide for VOC (Volatile Organic Compound) adsorption
CN107128932A
High-hydrophobicity organic modified natural zeolite and preparation method thereof
CN115724438A
Zeolite / silica sol based humidity adjusting ball and preparation method thereof
CN117797768A
Photocatalytically active natural zeolite in alkaline building material systems
EP2508478A1
Zeolite solidified body and solidifying method
JP2007063083A
Cited By
Preparation method and application of ultra-stable mineralization-based magnetic microspheres capable of removing soil heavy metal ions
CN116786077A
